English lecturers’ beliefs and practices in vocabulary learning - Alpino Susanto; Yunisa Oktavia; Sri Yuliani; Pipit Rahayu; Haryati Haryati; Tegor Tegor (Studies in English Language and Education, 2020)
Vocabulary has an important role in language learning at the college level, but in teaching practice, various obstacles are experienced by lecturers in implementing effective vocabulary learning. This study took place in Batam, Indonesia, and aims to investigate the English lecturers’ beliefs and practices in vocabulary learning; the phenomena of how they negotiate their teaching practices and what determines their choice of teaching methods when it comes to vocabulary learning. Five English lecturers from different universities were interviewed. The results of the interview were transcribed and analyzed based on the themes that appeared from data. The results showed that a requirement for practicality in class, curriculum, student atmosphere, and lecturers’ confidence in applying the right methods have effects on vocabulary learning. Lecturers have combined vocabulary learning with reading, writing, listening, and speaking in class. The main reference of a coursebook as the main guidance of the vocabulary learning varied between one class and another. All lecturers stated that they should find their own way to adopt external sources such as songs, vocabulary learning programs, and games to combine with their coursebook to beneficially meet the students’ preference. The new technology of teaching and learning is now part of classroom activities. Henceforth, this study concludes that the lecturers’ beliefs in the vocabulary learning approach are important. In practice, the lecturers need to combine them with various methods as the class situation do not always count on academic interests.